Investigation of terpinolene + ozone or terpinolene + nitrate radical reaction products using denuder/filter apparatus - Harrison, Joel C.; Wells, J.R. (Atmospheric environment (1994), 2013)
Terpinolene's (1-methyl-4-(propan-2-ylidene)cyclohexene) reaction with ozone or the nitrate radical was investigated using a denuder/filter apparatus in order to characterize gas-phase and particulate reaction products. Identification of the reaction products (i.e., aldehydes, ketones, dicarbonyls and carboxylic acids) was made using two derivatization methods; O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine (PFBHA) to derivatize the carbonyl products or 3-Ethyl-1-[3-(dimethylamino)propyl]carbodiimide hydrochloride (EDC) and 2,2,2-trifluoroethylamine hydrochloride (TFEA) to derivatize the carboxylic acid products. Proposed carbonyl products for ozonolysis of terpinolene are: 4-methylcyclohex-3-en-1-one, 2-hydroxy-4-methylcyclohex-3-en-1-one, glyoxal, methyl glyoxal, 3-oxobutanal, and 6-oxo-3-(propan-2-ylidene)heptanal. Proposed carbonyl products for nitrate radical reaction of terpinolene are: 2-hydroxy-4-methylcyclohex-3-en-1-one, glyoxal, methyl glyoxal, and 4-oxopentanal. No carboxylic acid products were detected with either oxidizing reactant. •Determined and contrasted the products of the reaction of terpinolene with ozone or nitrate radical.•Products captured using a denuder/filter apparatus.•Reaction products identified using a dual derivatization method.